Humans as a service : the promise and perils of work in the gig economy - Adams-Prassl, Jeremias (Oxford : Oxford University Press, 2018)
Is crowdsourcing the future of work? This text offers a lively and critical account of the gig economy: its promises and realities, what is at stake, and how we can ensure that customers, workers, platforms, and society at large benefit from this global and growing phenomenon.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 2, 2018).
Keywords: Temporary employment -- Economic aspects; Labor market -- Economic aspects; Labor laws and legislation; Industry; Economics